Fundamentos teórico-filosóficos nos cadernos “Por Uma Educação do Campo” - Luna, Junior Cesar (Universidade Federal de São Carlos, 2021)
From the 1990s onwards, rural social movements, in particular the Landless Rural Workers Movement (MST) together with the Pastoral Land Commission (CPT) started a fundamental discussion in which they sought to understand the new scenario of categorical irruption of rural education. In this perspective, this thesis was developed in the Study and Research Group on Rural Education (GEPEC), in the Doctoral Course in Education at the Federal University of São Carlos (UFSCar), and its guiding theme is the theoretical-philosophical basis of this movement so important to national education. The question is: from a Marxist theoretical-philosophical point of view, is there coherence (convergences and divergences) about its understanding and application/use among the members of the “For an Rural Education” movement contained in its seven books? Is there coherence about the criticisms directed to the Marxist theoretical-philosophical foundation, in opposition to a supposed theoretical-philosophical eclecticism that supports the pedagogical orientation of Rural Education? The hypothesis is that the movement "For a Rural Education", in its eagerness to help emancipate rural people through education, contributed little ideologically to their emancipation, in the mold of Marxism, but rather brought it closer to an adjustment to capitalism. In our research, we obtained confirmation of this hypothesis after a thorough analysis of the philosophical concepts highlighted in the referred books.
Theoretical-philosophy foundations in the books "For a Rural Education"
Keywords: Fundamentos da Educação; Educação do campo; Materialismo histórico dialético; Fundamentals of education; Rural education; Historical dialectical materialism; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO